Original Research: Implementation of an Early Mobility Program in an ICU. (December 2015) - Fraser, Danielle; Spiva, LeeAnna; Forman, Wendy; Hallen, Caroline
Abstract : ABSTRACT: Objective: Research is needed to determine the feasibility of implementing a dedicated ICU mobility team in community hospital settings. The purpose of this study was to assess, in one such hospital, four nurse-sensitive quality-of-care outcomes (falls, ventilator-associated events, pressure ulcers, and catheter-associated urinary tract infections [CAUTIs]), as well as hospital costs, sedation and delirium measures, and functional outcomes by comparing ICU patients who received physical therapy from a dedicated mobility team with ICU patients who received routine care. Methods: We conducted a retrospective longitudinal study at a community acute care hospital; patients were randomly assigned to intervention or routine care groups. The mobility team screened patients Monday through Friday using a mobility algorithm to determine eligibility for participation in each early mobility session. Based on their strength, balance, hemodynamic stability, and ability to participate in early mobility activities, patients advanced through four progressively difficult phases of mobility. Data were collected and analyzed after patients were discharged from the hospital. Results: The 66 patients who received the mobility intervention had significantly fewer falls, ventilator-associated events, pressure ulcers, and CAUTIs than the 66 patients in the routine care group. The mobility group also had lower hospital costs, fewer delirium days, lower sedation levels, and improved functional independence compared with the routine care group. Patients in the mobility group got out of bed on 2.5 more days than patients in the routine care group. There were also no adverse events in the mobility group. Conclusions: It is feasible for a community hospital to create and implement a dedicated ICU mobility team. Early mobilization of ICU patients contributed to fewer delirium days and improved patient outcomes, sedation levels, and functional status. Abstract : The authors recount how early mobilization of critically ill patients by an independent ICU mobility team contributed to improvements in patient outcomes, sedation levels, and functional status.